The Effect of Geographical Inquiry Based on Learning Style Differentiation on Students’ Critical Thinking Skills - Nurani, Mentari Pradi Galih; Handoyo, Budi; Rashid, Salman; Meilana, Lisa Nikita (Future Space: Studies in Geo-Education, 2024)
Learning in the Merdeka Curriculum prioritizes differentiation strategies that adapt learning styles to student preferences in order to train critical thinking skills. The use of Geographical Inquiry and differentiation strategies is relevant to existing gaps, but the effect of the integration of these two things is not yet known. This research aims to determine the effect of Geographical Inquiry based on learning style differentiation on students' critical thinking abilities. The research method has a quasi-experimental design using a post-test only measurements. The research was carried out for three weeks in the odd semester of the 2023/2024 academic year. The research subjects were students of class XI IPS at SMAN 1 Singosari who were divided into experimental classes and control classes. Data collection through conducting post-tests on material on flora and fauna conservation efforts. Data processing uses parametric statistical techniques and the average results of the two classes are analyzed using the independent sample t-test. The findings reveal that Geographical Inquiry tailored to different learning styles enhances students' critical thinking skills, suggesting a need for educational strategies that accommodate individual learning preferences. This has broad implications for improving 21st-century skills across educational settings, potentially transforming how we prepare students for future challenges